2015
DOI: 10.1155/2015/670963
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Electroacupuncture for Functional Constipation: A Randomized, Controlled, Clinical Trial

Abstract: Background. Electroacupuncture (EA) has been reported to treat functional constipation (FC). The aim of this study was to investigate the efficacy and safety of EA with different needle insertion method for FC. Methods. Sixty-seven participants were randomly assigned to control (EA with shallow puncture) and EA (with deep puncture) groups. Every patient received 5 treatments per week in the first two weeks, then 3 treatments per week during the following six weeks. Complete spontaneous bowel movements (CSBM), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 12 publications
3
8
0
Order By: Relevance
“…However, our population was less constipated, according to the complete bowel emptying, abdominal pain, and bloating scores. Studies that included subjects according to Rome III criteria for functional constipation have had lower baseline values for complete bowel emptying 34 , 41 , 42 , 45-47 and higher baseline scores for abdominal pain 30 , 35 , 41 , 46 , 48 and bloating 30 , 41 , 48 versus our trial.…”
Section: Discussionmentioning
confidence: 61%
“…However, our population was less constipated, according to the complete bowel emptying, abdominal pain, and bloating scores. Studies that included subjects according to Rome III criteria for functional constipation have had lower baseline values for complete bowel emptying 34 , 41 , 42 , 45-47 and higher baseline scores for abdominal pain 30 , 35 , 41 , 46 , 48 and bloating 30 , 41 , 48 versus our trial.…”
Section: Discussionmentioning
confidence: 61%
“…In 12 studies with 1805 patients, 14 , 16 , 17 , 21 , 22 , 24 - 26 , 31 , 33 , 34 , 36 pooled PAC-QOL was 1.97 (95% CI: 1.70-2.24) ( Figure 5 ). Publication bias was not evident (Egger P = .28).…”
Section: Resultsmentioning
confidence: 99%
“…After screening 426 records for eligibility, 24 studies representing 3786 unique patients were included in the meta-analysis. 5 , 14 - 36 The most common reasons for study exclusion were attributable to absence of main outcome reporting or Rome III FC diagnosis. A flow diagram of study identification and selection is shown in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…LI11 and ST37 are the common used acupoints for functional gastrointestinal motility disorders [ 14 , 17 , 29 31 ]. In this study, acupoints of bilateral LI11 (Quchi, located at the midpoint between the lateral end of the transverse cubical crease and the lateral epicondyle of the humerus) and ST37 (Shangjuxu, located 6 cun below the lateral depression between the patellar and patellar ligament, one finger width lateral to the anterior crest of the tibia) were used.…”
Section: Methodsmentioning
confidence: 99%
“…Studies use ST37 (Shangjuxu) combined with LI11 (Quchi) for functional constipation patients are infrequent. Different stimulation frequencies are used in these studies, including 2 Hz/200 Hz [ 15 ], 2 Hz/100 Hz [ 16 ], 2 Hz/15 Hz [ 17 , 18 ], 2 Hz/10 Hz [ 19 ], and 10 Hz/50 Hz [ 20 ]. The frequency of 2/50 Hz is rarely used.…”
Section: Introductionmentioning
confidence: 99%